STRATEGI PROGRAMMING INEWS DALAM MEMPERTAHANKAN PROGRAM SIARAN BERITA MENJELANG ASO 2022 - Romaria, Gustina; Astuti, Sri Wahyuning (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
This research concentrates on the realm of television studies as an institution, to find out how the strategy of the iNews Siang news program is in maintaining news broadcast programs ahead of ASO 2022. The type of research used is descriptive qualitative research. The object of this research study is the iNEWS Afternoon program ahead of the Migration policy of Analog TV broadcasts to Digital TV broadcasts or Analog Switch Off (ASO). The problems in this study are dissected by analyzing how the strategy of the iNews Siang news program is in maintaining the news broadcast program ahead of ASO 2022, data collection techniques are applied to support information by conducting observations, interviews, and documents. The purpose of this research is to find out the strategy for the INEWS Siang news program in maintaining the news broadcast program ahead of ASO 2022, through the pre-production, production and postproduction stages observed as one unit in a series of program strategies. Participatory observation methods, interviews and literature on the news department, Morrisan's program strategy theory were built as a framework for the approach. The results obtained are iNews TV station programming strategy, especially in the iNews Afternoon Towards ASO 2022 program in broadcasting television broadcast programs to digital so that they can reach all audiences throughout Indonesia. Therefore, there are programs broadcast by the iNews Siang program in preparation for or ahead of ASO 2022. ASO stands for Analog Switch Off. The policy of discontinuing Analog TV broadcasts to be subsequently transferred to digital TV broadcasts is known as Analog Switch Off (ASO). Keywords: ASO, iNEWSTV, digital broadcast, programming strategy, television journalist